Making good on a call to expand method choice for young people - Turning rhetoric into reality for addressing Sustainable Development Goal Three - Fariyal Fatma Fikree; Catharine Lane; Callie Simon; Gwyn Hainsworth; Patricia MacDonald (BMC, 2017)
Abstract Background Investments in the nearly two billion young people, aged 10-24 years, in the world today are necessary to meet global development commitments, specifically the Sustainable Development Goals and Ending Preventable Child and Maternal Deaths. More than 12 million married and unmarried adolescents (aged 15-19) will give birth in 2016. Complications of pregnancy and childbirth are the second leading cause of death among 15-19 year-old women and early childbearing can significantly curtail social and economic prospects for young women. Facilitating the ability of sexually active young people to choose and effectively use a satisfactory contraceptive method will ensure they can exercise their right to prevent, delay or space pregnancy. The Global Consensus Statement, "Expanding Contraceptive Choice for Adolescents and Youth to Include Long Acting and Reversible Contraception" provides evidence on the safety and effectiveness of LARCs for young people. Three inter-dependent actions linking advocacy and policy (advocating for policy and guideline revisions); supply (improving quality and accessibility of an expanded method choice) and an enabling environment (social norms and comprehensive reproductive health information) are suggested as vital to achieving full access and full choice for all sexually active young people. Identified approaches include national advocacy addressing policy guidelines and standard operating procedures that guide providers in the provision of age and developmentally appropriate contraceptive services; pre-service and in-service training for health care providers to be able to effectively communicate and counsel young people, including dispelling myths and misconceptions around LARCs; and partnering with young people to design appropriate, contextually-relevant, and effective strategies to increase their self-efficacy and, at the community level, address broader social norms to dispel stigma and discrimination. Conclusion An immediate call to action for collaborative and coordinated global, regional and national efforts that enable full access and full choice for all young people is paramount to achieve their reproductive health intentions and the Sustainable Development Goal targets.